Linguistic Means of Negation in Kartvelian Languages - Kurdadze, Ramaz; Tvaltvadze, Darejan; Lomia, Maia; Margiani-Subari, Ketevan; Zekalashvili, Rusudan (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2016)
This article is dedicated to one of the topical issues of linguistics –the means of linguistic expression of negation in the Kartvelian (Georgian, Megrelian, Laz, and Svan) languages. This type of research, from the typological point of view, is conducted for the first time; based on the data taken from old and modern Georgian and unwritten Kartvelian languages grammatical models of negative pronouns and adverbs are singlued out andanalysed with particular emphasis on the expression of the double negation and normalisation issues related to it in the modern literary (standard) Georgian language. The empirical material of the corpus-based and printed texts is processed in the diachronic and synchronic contexts, employing descriptive-statistical, historical and comparative methods. Frequency of the use of linguistic means expressing negation is also estimated. By comparison and collation of the research results, common Kartvelian consistent patterns and the specifics of each of the Kartvelian languages, in this regard, are revealed.